Effects of Supplementation of Inulin and Yeast Autolysate (Saccharomyces cerevisiae) on the Productive Performance, Egg Quality, Intestinal Morphology, and Microflora of Laying Japanese quails - Ayesheh Pourangha; Mohammad Taher Mirakzehi; Hassan Saleh (پژوهشهای تولیدات دامی)
Extended Abstract Background: The use of antibiotics in poultry feed has been banned or severely restricted in many countries due to the development of antibiotic resistance and threats to human health. Therefore, there has been a significant focus on alternative feed additives, such as probiotics, prebiotics, synbiotics, organic acids, and herbal products. Prebiotics are specific dietary fibers that cannot be directly digested by the bird's digestive system but serve as food for beneficial gut bacteria, promoting their growth and proliferation. By increasing the population of these beneficial bacteria, the gut environment is altered in a way that inhibits the growth of harmful bacteria and strengthens the bird's immune system. Consequently, the use of prebiotics in poultry feed leads to improved digestion and nutrient absorption, increased growth, a strengthened immune system, reduced disease incidence, and ultimately increased production and improved product quality. Probiotics are live microorganisms that, when added to poultry feed, alter the microbial balance of the gut in favor of beneficial bacteria. These beneficial bacteria produce short-chain fatty acids, strengthen the immune system, improve digestion and nutrient absorption, and reduce the growth of pathogenic bacteria, contributing to gut health and overall bird performance. As a result, the use of probiotics in poultry feed leads to increased growth, improved feed conversion ratio (FCR), reduced mortality, and improved carcass quality. In this context, inulin and yeasts such as Saccharomyces cerevisiae, which are classified as prebiotics and probiotics, respectively, have shown beneficial effects on improving poultry performance. Methods: This experiment was performed as a 2 × 2 factorial arrangement, using a total of 240 Japanese laying quails (Coturnix japonica) at 45 days of age in a completely randomized design with four treatments, six replicates per treatment, and 10 birds per replicate. The factors were inulin (0 and 15 g/kg) and yeast autolysate (S. cerevisiae) (0 and 1.5 g/kg). The birds were placed in the experimental cages for one week prior to the start of the experiment for adaptation and fed a commercial diet. The experimental period lasted 7 weeks, and the birds had ad libitum access to feed and water during the entire experimental period. The experimental diets were formulated to have similar AMEN and crude protein. Egg production (number and weight) was recorded daily, and feed intake was calculated weekly. At the end of the experiment, the FCR was calculated by dividing the feed consumed (in grams) by the produced egg mass (in grams). The eggs collected in the last 4 days of the experiment were used to determine the quantitative and qualitative characteristics of the eggs. One bird per replicate was randomly selected, bled, and then slaughtered on the final day of the experimental period. Samples were collected from the jejunum tissue for histological examination and from the ileum content for microbial population analysis. Results: The results of this experiment demonstrated that supplementation with autolyzed yeast led to a decrease in feed intake (p < 0.05). The addition of inulin and autolyzed yeast to the diet resulted in an increase in egg production and mass, as well as an improvement in FCR (p < 0.05). A significant interaction was observed between inulin and autolyzed yeast on egg production (p < 0.05). This interaction indicated that adding yeast to diets without inulin resulted in a significant increase in egg production (p < 0.05). Additionally, adding inulin to diets without yeast resulted in a significant increase in egg production (p < 0.05). Autolyzed yeast significantly increased egg weight and shell thickness (p < 0.05). No significant main effects of inulin or interaction effects between the two supplements were observed on egg quantitative and qualitative traits (P > 0.05). Histological findings showed that autolyzed yeast significantly increased villus length and the ratio of villus length to crypt depth (p < 0.05). No significant main effects of inulin or interaction effects were observed between the two supplements on jejunal morphology (p > 0.05). The results showed that supplementation with inulin and autolyzed yeast increased the population of lactobacillus and decreased the population of Clostridium perfringens, coliforms, and total anaerobic bacteria in the ileum (p < 0.05). The interaction between inulin and yeast showed that adding yeast to diets containing inulin resulted in a significant decrease in the coliform population in the ileum (p < 0.05). Analysis of blood parameters showed that supplementation with autolyzed yeast significantly reduced serum cholesterol levels (p < 0.05). Conclusion: Overall, the results of this experiment demonstrated that both inulin and autolyzed yeast supplements, at levels of 15 and 1.5 grams per kilogram of diet, respectively, either individually or in combination, had a positive impact on the production performance of quails. The improvement in the gut structure by autolyzed yeast and the alteration of gut microbiota toward an increase in beneficial bacteria by both supplements indicate their synergistic effects. These findings suggest that the combined use of these two supplements can be an effective nutritional approach to enhance the health and production performance of quails.